Simulation of turbulent non-premixed combustion in pulverized coal from Kalimantan Indonesia - Agus Prasetyo Nuryadi; Chairunnisa Chairunnisa; Fitrianto Fitrianto; M.P. Helios; R.T. Soewono; R.J. Komara; I. Wulandari (Politeknik Negeri Lhokseumawe, 2023)
A computational simulation was created to investigate pollutants during coal combustion in a Drop Tube Furnace using Kalimantan coal. Previous research has explored Drop Tube Furnace combustion with Kalimantan coal, but lacked an understanding of combustion phenomena and pollutants, which are challenging to observe experimentally. This study utilized three samples of Kalimantan coal, namely RP, MB, and KC, acquired from various mining sources. This research is new study of simulation combustion coal in Drop Tube Furnace using non-premixed turbulent combustion and the Probability Density Function model with structured grid. The study reports on the temperatures and mass fractions of pollutants, including NOX, SO2, and CO2, along the centerline of the domain. The findings show that RP coal produced the highest combustion temperature, while KC coal produced the lowest. MB coal had the highest CO2 mass fraction, KC coal had the highest NOx value, and RP coal had the highest SO2 value.